Implementasi Augmented Reality Sebagai Media Pengenalan Perangkat Jaringan Komputer Menggunakan Metode Marker Based Traking Berbasis Android Studi Kasus SMK Prudent School - Aldi Wibi Kusumah; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2023)
Technological developments have an effect on aspects of education that have an impact on learning activities. In computer network learning, there is still at least the use of media that has an impact on students' understanding of the material for computer network devices. Augmented Reality is the incorporation of two-dimensional or three-dimensional virtual objects into a real three-dimensional environment, then projecting these virtual objects in real time. By utilizing the computer or smartphone, many technology-based products can be made. Augmented Reality-based applications with marker-based tracking techniques become a solution in practicing computer network devices at Prudential School Vocational Schools, especially for class 10 computer network engineering at Prudential School Vocational Schools for users, both for teachers and students. The concept of this application is the introduction of computer network devices at Prudential School Vocational Schools through the camera installed on the user's smartphone. by pointing the smartphone camera at the marker the user will get information about the desired computer network device.